Effect of aqueous extract of Ardisia colorata Roxb. leaves on blood sugar in Albino rats - Ningthoujam, Geetanjali; Datta, Swagata; Zosangpuii, Christina; Meena, Nameirakpam; Medhabati, Mayanglambam (International Journal of Research in Medical Sciences, 2024)
Background: Diabetes is a group of common metabolic disorders that share the characteristic features of hyperglycemia. Ardisia colorata Roxb. leaf extract (AEAC) is reported to be used for the treatment of diabetes. So, the present study is undertaken to evaluate the effect of Ardisia colorata Roxb. leaves on blood sugar by using different hyperglycemic models in Albino rats. Methods: In both the glucose induced hyperglycemia model and streptozotocin induced hyperglycemia model, animals were divided into 4 groups of 6 animals each. 2% gum acacia were taken as control (group 1) and glimepiride 0.2 mg/kg were taken as standard (group 2). Hyperglycemic activity was checked at two different doses i.e., 200 mg/kg (test 1) and 400 mg/kg (test 2) of AEAC (given at group 3 and group 4 respectively) by assessing the decreased in blood sugar level using glucometer by following methods of these two models. The results were analyzed using one-way analysis of variance (ANOVA) followed by Bonferroni test. P value <0.05 was considered significant. Results: Test 2 showed significant reduction in blood sugar level when compared to control after 1 hour and 2 hours of drug administration in both the models whereas test 1 showed significant reduction only in glucose induced hyperglycemia model. There was significant difference when test 2 was compared to test 1 after 1 hour and 2 hours in both the models. Conclusions: The present studies showed that AEAC leaves produced significant reduction in blood sugar level. It might be suggested that flavonoids, alkaloids, tannins and terpenoids were responsible for the hypoglycemic activity of AEAC leaves.